NOTAS SOBRE SERIOLA FASCIATA (BLOCH) (PISCES: CARANGIDAE) EN LA REGION DE SANTA MARTA, CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
Information is presented about four specimens of the poorly known lesser amberjack, Serióla fasciata, collected in the Santa Marta area, Colombian Caribbean.